SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA PERIKANAN - Putri Sari Nilam Cayo (Justici, 2022)
Illegal fishing, both by individuals and by corporations, has been increasing and is very concerning. Various modus operandi is carried out by national and foreign vessels to illegally fish in the Indonesian maritime jurisdiction. This is clearly contrary to national law and international law. The criminal sanctions for perpetrators of criminal acts in the field of fisheries (illegal fishing) can be punished with a maximum imprisonment 10 (ten years) and a maximum fine of Rp. 2,000,000,000.00 (two billion rupiah) as regulated in Article 84 paragraph (2) and paragraph (4) of the Law Fishery